Inflammatory Markers and Incidence of Hospitalization With Infection in Chronic Kidney Disease: The Chronic Renal Insufficiency Cohort Study. Issue 5 (1st November 2019) - Ishigami, Junichi; Taliercio, Jonathan; I Feldman, Harold; Srivastava, Anand; Townsend, Raymond; L Cohen, Debbie; Horwitz, Edward; Rao, Panduranga; Charleston, Jeanne; Fink, Jeffrey C; Ricardo, Ana C; Sondheimer, James; et al.
Abstract: Persons with chronic kidney disease (CKD) are at high risk of infection. While low-grade inflammation could impair immune response, it is unknown whether inflammatory markers are associated with infection risk in this clinical population. Using 2003–2013 data from the Chronic Renal Insufficiency Cohort Study (3, 597 participants with CKD), we assessed the association of baseline plasma levels of 4 inflammatory markers (interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α ), interleukin-1 receptor antagonist (IL-1RA), and transforming growth factor-β (TGF-β )) with incident hospitalization with major infection (pneumonia, urinary tract infection, cellulitis and osteomyelitis, and bacteremia and sepsis). During follow-up (median 7.5 years), 36% ( n  = 1, 290) had incident hospitalization with major infection. In multivariable Cox analyses with each inflammatory marker modeled as a restricted cubic spline, higher levels of IL-6 and TNF-α were monotonically associated with increased risk of hospitalization with major infection (for 95th vs. 5th percentile, hazard ratio = 2.11 (95% confidence interval: 1.68, 2.66) for IL-6 and 1.88 (95% confidence interval: 1.51, 2.33) for TNF-α ), while corresponding associations for IL-1RA or TGF-β were nonsignificant. Thus, higher plasma levels of IL-6 and TNF-α, but not IL-1RA or TGF-β, were significantly associated with increased risk of hospitalization with major infection. Future studies should investigate whether inflammatory pathways that involve IL-6 and TNF-α increase susceptibility to infection among individuals with CKD.